2017
DOI: 10.1111/pce.13023
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase Dδ negatively regulates plant thermotolerance by destabilizing cortical microtubules in Arabidopsis

Abstract: The pattern of cortical microtubule arrays plays an important role in plant growth and adaptation in response to hormonal and environmental changes. Cortical microtubules are connected with the plasma membrane (PM); however, how the membrane affects cortical microtubule organization is not well understood. Here, we showed that phospholipase Dδ (PLDδ) was associated with the PM and co-localized with microtubules in cells. In vitro analysis revealed that PLDδ bound to microtubules, resulting in microtubule disor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 55 publications
0
30
3
Order By: Relevance
“…In Arabidopsis, PLDa and PLDd are the most abundant PLDs, and their activities increase upon exposure to salt stress (Bargmann et al, 2009;Yu et al, 2010;Zhang et al, 2012b). The absence of PLDs in plda1, pldd-1, and pldd-2 single mutants and in plda1 pldd-1 and plda1 pldd-2 double mutants was verified by immunoblotting using anti-PLDa1 and anti-PLDd antibodies ( Figure 1A; Guo et al, 2012;Zhang et al, 2012bZhang et al, , 2017. Deletion of PLDa1 or PLDd decreased total PLD (PLDa1 and PLDd) activity, and PLD activity was decreased markedly in the plda1 pldd-1 and plda1 pldd-2 double mutants ( Figure 1B).…”
Section: Decreased Pa Content and Increased Sensitivity To Nacl In Plmentioning
confidence: 91%
See 3 more Smart Citations
“…In Arabidopsis, PLDa and PLDd are the most abundant PLDs, and their activities increase upon exposure to salt stress (Bargmann et al, 2009;Yu et al, 2010;Zhang et al, 2012b). The absence of PLDs in plda1, pldd-1, and pldd-2 single mutants and in plda1 pldd-1 and plda1 pldd-2 double mutants was verified by immunoblotting using anti-PLDa1 and anti-PLDd antibodies ( Figure 1A; Guo et al, 2012;Zhang et al, 2012bZhang et al, , 2017. Deletion of PLDa1 or PLDd decreased total PLD (PLDa1 and PLDd) activity, and PLD activity was decreased markedly in the plda1 pldd-1 and plda1 pldd-2 double mutants ( Figure 1B).…”
Section: Decreased Pa Content and Increased Sensitivity To Nacl In Plmentioning
confidence: 91%
“…The homozygous lines were confirmed by PCR. The homozygous pld mutants (plda1, pldd-1, pldd-2, and pldz2) and wag2 (SALK_070240) were described previously (Li et al, 2006;Zhang et al, 2012bZhang et al, , 2017Miao et al, 2018). The pid mutant is sterile and therefore must be propagated as a heterozygote.…”
Section: Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, conflicting results were obtained in a later study, which found that cortical microtubule remained attached to the plasma membrane of tobacco BY-2 protoplasts after treatment with n-butanol (Hirase et al, 2006). Recently, heat shock was found to activate PLD, in which microtubules dissociated from the plasma membrane and became destabilized, leading to the disorganization of cortical arrays (Zhang et al, 2017). In addition to PLD, cortical microtubules partially detach from the membrane and exhibit extensive waving in clasp-1 cells due to cytoplasmic streaming before reattaching to the membrane (Ambrose and Wasteneys, 2008).…”
Section: Microtubule Interactions With the Plasma Membrane And Other mentioning
confidence: 87%